2021
DOI: 10.54718/yset8449
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges: Improving Extension Support to Organic Growers in North Georgia

Abstract: Organic agriculture has the potential to improve the environmental performance of U.S. agriculture, supporting increasing food demand and diversification of food consumption while improving the quality of ecosystems. Organic growers are challenged by a lack of Cooperative Extension agent support as agents have not served organic growers to the same extent as conventional growers nationwide. Rogers’ (2003) diffusion of innovations theory guided our phenomenological inquiry to explore (a) what agents experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, the identification of other farmers as primary resources indicates that integrating growers as co-educators into organic programming can enhance the impact of these programs by building trust, relevance and credibility (Wyckhuys and Oõneil, 2007; Kuehne et al ., 2017; Bardenhagen et al ., 2020). Increasing these bidirectional modes of engagement between Extension agents and organic growers as co-educators and co-creators of knowledge has been identified as a method to not only improve Extension resources for organic production, but also positively influence the communication and adoption of effective preventive pest management strategies within organic systems (Sarker and Itohara, 2009; Bardenhagen et al ., 2020; Marabesi et al ., 2021). Thus, university Extension programs may be improved by developing research, workshops, conferences, and resources in close partnership with grower stakeholders (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the identification of other farmers as primary resources indicates that integrating growers as co-educators into organic programming can enhance the impact of these programs by building trust, relevance and credibility (Wyckhuys and Oõneil, 2007; Kuehne et al ., 2017; Bardenhagen et al ., 2020). Increasing these bidirectional modes of engagement between Extension agents and organic growers as co-educators and co-creators of knowledge has been identified as a method to not only improve Extension resources for organic production, but also positively influence the communication and adoption of effective preventive pest management strategies within organic systems (Sarker and Itohara, 2009; Bardenhagen et al ., 2020; Marabesi et al ., 2021). Thus, university Extension programs may be improved by developing research, workshops, conferences, and resources in close partnership with grower stakeholders (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found that growers emphasize learning from their own experiences and those of other farmers rather than Extension agents and scientific research, which are often viewed as grounded in conventional management approaches (Eckert and Bell, 2005; Agunga and Igodan, 2007; Middendorf, 2007; Parker and Lillard, 2013; Jabbour et al ., 2014; Crawford et al ., 2015; Marabesi et al ., 2021). Growers responding to our surveys also placed less emphasis on Extension resources as compared to other knowledge and training opportunities regarding the development of their disease management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations